Low Pollution Emission to Purify Fuel Cell Technology Comprehensively: A Review - Muhaned Mohammed Eteya1 , Hayder Saleh Mahdi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In recent decades, scientists have been urged to build the new energy resources by depleting fossil fuel,high-energy demand and pollution. Being one of the principal alternative power devices, Thanks to thehigh energy conversion efficiency, the fuel cells have attracted growing attention, simple operation andlow pollution emissions. This paper surveys the historical backdrop of the power devices, the energy unitactivity, and sorts of energy units, their points of interest, inconveniences and applications.